Evaluation of pathogenic variants detected in high homology regions of the PMS2 gene. How effective is long-range PCR? - Paixão, Daniele; Lima, Thalitta Hetamaro Ayala; de Souza, Rafaela Rogério Floriano; Carnavalli, Juliana Emilia Prior; Picanço-Albuquerque, Clarissa Gondim; Silva-Fernandes, Isabelle Joyce de Lima; de Barros Silva, Paulo Goberlânio; Mitne-Neto, Miguel; Moreira, Caroline Mônaco; Baratela, Wagner Antônio da Rosa (Frontiers in Oncology, 2024)
Introduction: Lynch syndrome (LS) is an inherited cancer predisposition syndrome characterized by a high risk of colorectal and extracolonic tumors. Germline pathogenic variants (GPV) in the PMS2 gene are associated with less than 15% of all cases. The PMS2CL pseudogene presents high homology with PMS2, challenging molecular diagnosis by Next Generation Sequencing (NGS). Due to the high methodological complexity required to distinguish variants between PMS2 and PMS2CL, most laboratories do not clearly report the origin of this molecular finding.The aim of this study was to confirm the GPVs detected by NGS in regions of high homology segments of the PMS2 gene in a Brazilian sample.Methods: An orthogonal and gold standard Long-Range PCR (LR-PCR) methodology to separate variants detected in the PMS2 gene from those detected in the pseudogene.Results: A total of 74 samples with a PMS2 GPV detected by NGS in exons with high homology with PMS2CL pseudogene were evaluated. The most common was NM_000535.6:c.2182_2184delinsG, which was previously described as deleterious mutation in a study of African-American patients with LS and has been widely reported by laboratories as a pathogenic variant associated with the LS phenotype. Of all GPVs identified, only 6.8% were confirmed by LR-PCR. Conversely, more than 90% of GPV were not confirmed after LR-PCR, and the diagnosis of LS was ruled out by molecular mechanisms associated with PMS2.In conclusion, the use of LR-PCR was demonstrated to be a reliable approach for accurate molecular analysis of PMS2 variants in segments with high homology with PMS2CL. We highlight that our laboratory is a pioneer in routine diagnostic complementation of the PMS2 gene in Brazil, directly contributing to a more assertive molecular diagnosis and adequate genetic counseling for these patients and their families.